Hyperstar Polyester‐Based Functional Nanotheranostics for the Targeted Drug Delivery and Treatment of Cancer. Issue 12 (16th October 2019) - Alnasser, Riyadh; Shaw, Zachary; Santra, Santimukul
Abstract: In this study, we have synthesized new class of hyperstar polyester (HSPE) polymer using a functional A2 B monomer and bio‐based sorbitol. We hypothesize that by incorporating sorbitol, its amphiphilic nature will give the polymer greater solubility and allow for the encapsulation of wide range of anti‐cancer therapeutics. We used potassium methoxide to catalyze the melt polymerization reaction. Using the solvent diffusion method, this polymer was used to construct polymeric nanoparticles to encapsulate therapeutics, in one step, for monitoring drug delivery and treatment. The cytotoxicity of our HSPE nanoparticles was evaluated by a cell‐based MTT assays using prostate cancer cells (LNCaP) and healthy cells (CHO). In addition, the level of internalization of our HSPE nanoparticles was evaluated using fluorescence microscopy. Results showed the HSPE nanoparticles have the capability to target and concurrently image and kill cancer cells. Taken together, these studies indicate the successful development of a new drug delivery system and demonstrated its potential use in the pharmaceutical industry and the field of medicine. Abstract : A soft drug delivery system is formulated from a newly designed amphiphilic hyperstar polyester polymer. This biocompatible nanotheranostic system can effectively encapsulate anti‐cancer therapeutics and deliver specifically to tumor cells.